TThe Influence of Social Media on Religious Perceptions and Behaviors - Rahman, Abdul; Harahap, Suheri (Reflection Journal, 2025)
This study examines the influence of social media on religious perceptions and behaviors among university students in Medan City within the context of digital religiosity. Employing a qualitative research design with an interpretative phenomenological approach, data were collected through in-depth interviews with ten active university students who regularly access religious content on social media platforms. The findings indicate that social media has become a primary source of religious information and spiritual engagement for students, shaping their understanding of religious values, tolerance, and ethical conduct. Exposure to digital religious content contributes to positive behavioral changes, including increased motivation for worship, enhanced moral self-regulation, and greater spiritual awareness. However, the study also reveals the ambivalent nature of digital religiosity. Alongside its constructive potential, social media presents significant challenges, such as interpretive confusion, misinformation, and exposure to intolerant or polarized religious narratives. These challenges are exacerbated by the lack of clear religious authority in digital spaces and the algorithmic tendencies of social media platforms that reinforce echo chambers.The study underscores the importance of strengthening Religious Digital Literacy to enable students to critically engage with online religious content and to foster inclusive, moderate, and reflective forms of religiosity in the digital era.